THE EFFECT OF ESG PERFORMANCE ON MARKET VALUE WITH CSR COMMITTEE AS A MODERATING VARIABLE (Evidence from Companies Listed on the Indonesia Stock Exchange, 2020-2024) - Muhammad Maliq Akeem; Dwi Ratmono (Diponegoro Journal of Accounting, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on market value and the moderating role of the Corporate Social Responsibility (CSR) Committee in companies listed on the Indonesia Stock Exchange during 2020-2024. Two ESG measurement approaches are applied to address concerns about ESG rating divergence: standardized ESG Scores obtained from Refinitiv and ESG content analysis based on the Global Reporting Initiative Standards. Purposive sampling produced 375 firm-year observations for the Refinitiv model and 465 firm-year observations for the disclosure-based model. Both models were estimated using panel data regression and the Fixed Effect Model. The results show that Refinitiv ESG Scores have a significant negative effect on market value, whereas GRI-based ESG content analysis has no significant effect. The CSR Committee has no significant moderating effect in either model. In the disclosure-based model, the committee has a negative direct association with market value, while profitability is positively associated with market value. These findings indicate that ESG performance has not yet become a consistent determinant of valuation in the Indonesian capital market. They also provide evidence that differences in ESG measurement can produce different empirical conclusions and that the formal existence of a CSR Committee does not necessarily increase the value relevance of ESG performance.